N6‐methyladenosine‐modified HOTAIRM1 promotes vasculogenic mimicry formation in glioma. Issue 1 (27th October 2022) - Wu, Zhangyi; Lin, Yihai; Wei, Nan
Abstract: Vasculogenic mimicry (VM) has been reported to accelerate angiogenesis in malignant tumors, yet the mechanism underlying VM has not been fully elucidated. N6‐methyladenosine (m6A) mainly modulates mRNA fate and affects multiple tumorigenesis. Here, we aimed to investigate m6A‐modified HOXA transcript antisense RNA myeloid‐specific 1 (HOTAIRM1) in the regulation of glioma‐associated VM formation. Gene expression was analyzed by quantitative RT‐PCR. Cell viability, metastases, and VM formation capacity were determined by CCK‐8, migration and invasion, as well as tube formation assays, respectively. The function and mechanisms of m6A‐modified HOTAIRM1 were defined through liquid chromatography–tandem mass spectrometry m6A quantification, methylated RNA immunoprecipitation sequencing, RNA stability assays, and RNA pull‐down experiments. A glioma xenograft mouse model was further established for VM evaluation in vivo. The results showed that HOTAIRM1, methyltransferase‐like 3 (METTL3), and insulin‐like growth factor binding protein 2 (IGFBP2) were upregulated in glioma tissues and cell lines. HOTAIRM1 functions as an oncogene in glioma progression; however, knockdown of HOTAIRM1 significantly reduced cell viability, migration, invasion, and VM formation. Notably, METTL3‐dependent m6A modification enhanced HOTAIRM1 mRNA stability, whereas knockdown of METTL3 deficiency significantly suppressed VM in glioma. Moreover, HOTAIRM1 was found to bind IGFBP2, and HOTAIRM1 deficiency blocked glioma progression and VM formation in vivo. Our results indicated that METTL3‐dependent m6A‐modified HOTAIRM1 promoted VM formation in glioma. Abstract : METTL3‐dependent m6A‐modified HOTAIRM1 promoted VM by targeting IGFBP2 in glioma progression.